Dietary free L-glutamate contributes to maintaining a low sodium intake among Vietnamese - Hien, Vu Thi Thu; Tuyen, Le Danh; Wakita, Andrea; Shikanai, Saiko; Hang, Le Thi; Anh, Nguyen Thi Diep; Nguyet, Nguyen Thi Anh; Iwamoto, Tamami; Matsumoto, Hideki; Uneyama, Hisayuki; Son, Nguyen Vu; Linh, Nguyen Nhat; et al. (Frontiers in Nutrition, 2024)
Background: WHO and FAO recommend the consumption of less than 2,000 mg of sodium/day to reduce blood pressure and the risk of conditions, such as, cardiovascular disease and coronary heart diseases. The sodium intake among Vietnamese was reported to be 7,200 mg/d or more. Free L-glutamate has flavor when it is added to food and improves the taste of sodium-reduced foods. Objective: To investigate if the intake of free L-glutamate-rich seasonings contributes to maintaining a low sodium intake in a cross-over study Methods: From a total of 145 subjects, 42 participants were screening for participation in the crossover design study. Subjects were randomly allocated to low free L-glutamate group (Low free L-Gl) and normal free L-glutamate group (Normal free L-Gl). Both received a direct educational guideline to reduce sodium intake. The Low free L-Gl group started with a restriction in the variety of free L-glutamate-rich seasonings and the Normal free L-Gl group had no restriction in the variety of seasoning. The chromogranin-A (CgA pmol/mg protein) was measured to assess the stress level. Blood pressures were measured at week 0 (baseline), week 2, week 4 and week 6, while body weight, height, urine sodium and potassium excretion, chromogranin-A (CgA pmol/mg protein) from saliva and free L-glutamate from food were measured at week 0, 3 and 6.In Low free L-Gl , the amount of free L-glutamate in food decrease significantly from baseline to week 6 (p < 0.001), while it did not change in the Normal free L-Gl (p > 0.05). However, the reduction of sodium excretion at week 6 was 22% in Low free L-Gl (5,875 mg/d vs 4,603 mg/d, p < 0.01) and 46% in Normal free L-Gl (6,107 mg/d vs. 3,277 mg/d, p < 0.00), both lower than the baseline. CgA (pmol/mg protein) did not show any difference between the two groups. The group with Normal free L-Gl intake showed a 46% reduction in sodium excretion by week 6 compared to the baseline. This suggests that the consumption of L-glutamate-rich seasonings, when complemented with direct educational guideline, can contribute to reduce sodium intake